2017
DOI: 10.1371/journal.pone.0177518
|View full text |Cite
|
Sign up to set email alerts
|

Rice black streaked dwarf virus P7-2 forms a SCF complex through binding to Oryza sativa SKP1-like proteins, and interacts with GID2 involved in the gibberellin pathway

Abstract: As a core subunit of the SCF complex that promotes protein degradation through the 26S proteasome, S-phase kinase-associated protein 1 (SKP1) plays important roles in multiple cellular processes in eukaryotes, including gibberellin (GA), jasmonate, ethylene, auxin and light responses. P7-2 encoded by Rice black streaked dwarf virus (RBSDV), a devastating viral pathogen that causes severe symptoms in infected plants, interacts with SKP1 from different plants. However, whether RBSDV P7-2 forms a SCF complex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 69 publications
0
28
0
1
Order By: Relevance
“…Sun, Zhang, et al, ). S7‐2 encodes a component of the SCF (Skp, Cullin, F‐box) complex (Tao et al, ). Segments S8 and S10 encode a core capsid protein and an outer capsid protein (Liu, Wei, Zhong, & Li, ; Liu, Wei, Zhong, & Li, ; Z.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun, Zhang, et al, ). S7‐2 encodes a component of the SCF (Skp, Cullin, F‐box) complex (Tao et al, ). Segments S8 and S10 encode a core capsid protein and an outer capsid protein (Liu, Wei, Zhong, & Li, ; Liu, Wei, Zhong, & Li, ; Z.…”
Section: Introductionmentioning
confidence: 99%
“…S7-1 encodes a tubular protein and is localized in the PD of plant cells (Isogai, Uyeda, & Lee, 1998;. S7-2 encodes a component of the SCF (Skp, Cullin, F-box) complex (Tao et al, 2017).…”
mentioning
confidence: 99%
“…Another protein of RBSDV, P7–2, functions as a key subunit of Skp1/Cul1/F-box complex ubiquitin ligase by interacting with SKP1 [ 7 ]. In rice and maize, the P7–2 protein is also involved in gibberellin pathway by interacting with GID2 during the RBSDV infection [ 8 ]. P9–1 of RSBSDV is an alpha-helical protein that plays important roles in the early phase of virus life cycle by forming intracellular viroplasms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although interactions between viral factors and CRL components have been reported previously for DNA and RNA viruses (Zhang et al, 2001;Oh et al, 2006;Lozano-Duran et al, 2011;Fu et al, 2012), it is not clear whether CSN complexes can interact with RBSDV-encoded factor(s). A previous report by Tao et al (2017) showed that the RBSDV P7-2 protein functioned as an SCF complex component in rice. The authors suggested that the gibberellin signaling pathway might play a role in RBSDV infection in rice .…”
Section: Discussionmentioning
confidence: 97%